Untangling the Ties Between Social Cognition and Body Motion: Gender Impact - Isernia, Sara; Sokolov, Alexander N.; Fallgatter, Andreas J.; Pavlova, Marina A. (Frontiers in Psychology, 2020)
We proved viability of the general hypothesis that biological motion (BM) processing serves a hallmark of social cognition. We assumed that BM processing and inferring emotions through BM (body language reading) are firmly linked, and examined whether this tie is gender-specific. Healthy females and males completed two tasks with the same set of point-light BM displays portraying angry and neutral locomotion of female and male actors. On one task, perceivers had to indicate actor gender, while on the other, to infer emotional content of locomotion. Thus, with identical visual input, we directed task demands either to BM processing or to inferring of emotion. This design allows straight comparison between sensitivity to BM and recognition of emotions conveyed by the same BM. In addition, perceivers were administered a set of photographs from the Reading the Mind in the Eyes Test (RMET), with which they identified either emotional state or actor gender. Although there were no gender differences in performance on BM tasks, a tight link occurred between recognition accuracy of emotions and gender through BM in males. In females only, body language reading (both accuracy and response time) was associated with performance on the RMET. The outcome underscores gender-specific modes in visual social cognition, and triggers investigation of body language reading in a wide range of neuropsychiatric disorders.